O funcionamento da noção de língua em instrumentos midiáticos de divulgação linguística - Jurach, Ivanise (2011)
This master‟s dissertation aims to understand the language notion that circulates in media instruments of linguistics disclosure. To do so, we organized a file composed by some of these publisher instruments of teaching/learning languages of Idioms‟ Course and/or of linguistics movements, such as: folders, posters or electronic publish on the internet. We chose to investigate this subject because of the fact the language is distinguished by different designations; what trouble us were the different ways of refereeing to the English Language and the Esperanto; being these two languages, in special, that interested us. The reflections of this work has as theoretical reference the Discourse Analysis (DA) of French line. We are going to investigate the meanings movement about the language‟ definitions awarded in these materials in order to deconstruct the evidences which circulate these two languages in question. From this considerations, we‟ll try to operate with the politic and linguistic political notions that determine the productions and circulation of the meanings‟ effects about the language(s). Thereby, we divided the research in three parts named and constituted by the following way: in the Part I, Some pointed notions during the theoretical way , we presented the notions that will be developed at the long of our theoretical way, among which we pointed the subject, ideology and discourse; also mobilizing the imaginary formations, which are constitutive of the position-subject‟ taken so, after it, to understand the ways‟ movement from globalization to the world in view of these notions are determiners to the imaginary space that take up the languages in present times, XXI century. Have it done, we also approaches the religious‟ subject passage to juridical subject in the Middle Age, because, this is the passage we identify as one of capitalism‟ discourses founders around the language notion. In the Part II, Language and history: meanings effects , we operate with the constitutive historicity of English Language and of Esperanto trying to visualize the social-historical materiality by which these languages circulate media releases. At a last moment, in the Part III, The politic-ideological functioning of and about the languages , we‟ll investigate the politic and the ideology that rule the meanings effects in relation production on the languages, trying to explicit the different designations that circulate in the media instruments of linguistic disclosure to teaching/learning English Language and Esperanto.